2016
DOI: 10.1007/s00431-016-2724-8
|View full text |Cite
|
Sign up to set email alerts
|

The β-glucosidase assay: a new diagnostic tool for necrotizing enterocolitis. Sensitivity, specificity, and predictive values

Abstract: •NEC affects ∼2.5 % of infants at NICU, ∼90 % of them weighing <1500 g. •NEC requires a careful differential diagnosis, being lethal if not diagnosed and treated. What is new: •CBG assay will be useful to determine infants without NEC and preventing unnecessary treatment. •CBG assay could discriminate NEC better than other gut-specific sera protein biomarkers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Moreno J. L. et al and Benkoe T. et al have been shown to increase the tissue-specific enzyme β-glucosidase activity in blood plasma in children with diagnosed NEC [14,42]. Cytosolic β-glucosidase belongs to the widespread hydrolase family.…”
Section: Inflammation/ Intestinal Injurymentioning
confidence: 99%
See 2 more Smart Citations
“…Moreno J. L. et al and Benkoe T. et al have been shown to increase the tissue-specific enzyme β-glucosidase activity in blood plasma in children with diagnosed NEC [14,42]. Cytosolic β-glucosidase belongs to the widespread hydrolase family.…”
Section: Inflammation/ Intestinal Injurymentioning
confidence: 99%
“…Markers for early and differential diagnosis describe the main etiopathogenetic mechanisms of disease development. Markers characterizing intestinal tissue damage, specific inflammatory markers [13][14][15] come to the fore.…”
Section: Modern Systematics Neс With Etiopathogenesis Positionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of β-glucosidase is often used as an indicator to demonstrate qualitative changes in organisms. It has been reported as a potential biomarker for the early diagnosis of neonatal necrotizing enterocolitis (NEC) (Chen et al, 2012;Gómez-Chaparro Moreno et al, 2016) and as an alternative therapeutic strategy to overcome chemoresistance in breast cancer (Zhou et al, 2017). Furthermore, some Chinese herbal medicines, such as Semen Armeniacae Amarum (Zhao LY et al, 2017), Chrysanthemum morifolium (Zuo et al, 2015), and Scrophularia root (Yu et al, 2017), are studied by detecting β-glucosidase activity to reveal the mechanisms of active ingredient hydrolysis during periods of processing and storage.…”
mentioning
confidence: 99%